Space and Time : a Priori and A Posteriori Studies. - Fano, Vincenzo (Philosophische Analyse, 2014)
The articles in this volume focus on the ontology of space and time, including the themes of substantivalism vs. relationism, continuity vs. discreteness, and time travel. In the current debate on these issues, there is a tendency to separate too rigidly between a priori and a posteriori approaches. This volume aims to bridge the gap between these two perspectives, showing the fruitfulness of combining them to the greatest extent possible.